The Principle of Appropriateness as the Basis for Determining Interest Rates in Debt Agreements: Asas Kepatutan Sebagai Dasar Dalam Penetapan Bunga Dalam Perjanjian Utang Piutang - Eliza, Rahmi; Djumikasih; Suwardiyati, Rumi (WARKAT, 2025)
This research raises the issues related to the provisions on interest rates, especially in personal loan agreements, is left to the discretion of the contracting parties based on the principle of freedom of contract. Even though the law provides a framework for regulating interest in agreements to control unreasonable interest practices, it unfortunately does not specify the maximum rate that may be agreed upon. Therefore, the application of the principle of fairness plays an important role in assessing and determining reasonable interest rates by the parties. This research uses normative legal research and employs statutory and case approaches, using primary, secondary, and tertiary legal materials. Legal material search techniques in this study include literature review, website or internet study, and document study, with legal material analysis using systematic interpretations. The results of the study shows that the main factors considered by judges in assessing reasonable interest rates in loan agreements include the agreement of the parties, legal regulations, comparisons with banking practices, principles of fairness and justice, and protection for the weaker party. Currently, there are no regulations governing the maximum interest rate that may be agreed upon in loan agreements outside formal financial institutions. This legal vacuum creates uncertainty and opens the door for the practice of excessively high interest rates that may harm borrowers. The application of the principle of fairness in loan agreements serves as an important legal mechanism to maintain balance, justice, and legal protection for all parties.